The role of biomarkers in the early diagnosis of traumatic brain injury - Hassan, Nabiga Hassan; Osman, Islam Yousif A.; Osman, Nanci Ezeldin; Goda, Mawada Abdella Hassan; Balol, Mohammed Alameer Alameen Ahmed; Abdelah, Enas Muhieldeen; Ahmed, Amjad Osman; Gomaa, Emad Hamdy (International Journal Of Community Medicine And Public Health, 2025)
Traumatic brain injury (TBI) is a leading cause of mortality worldwide. It is caused by blunt force, explosive blasts, sudden head acceleration or deceleration, or penetrating trauma to the skull. TBI can be classified according to GCS into mild (GCS 13-15), moderate (GCS 9-12), and severe (GCS 3-8). Symptoms of TBI vary from mild symptoms to neurodegenerative diseases. Neuroimaging is the most utilized diagnostic tool in cases of TBI. However, its complex pathophysiology mechanisms make it difficult to diagnose TBI early. Biomarkers of TBI, such as glial cell injury biomarkers, axonal injury biomarkers, and inflammation biomarkers, are emerging as diagnostic and prognostic tools in TBI. However, the diagnostic and prognostic values of biomarkers showed mixed results. The aim of this review is to discuss the role of biomarkers in the early diagnosis of TBI in adults and children. Pathophysiology of TBI includes disruption of blood-brain barrier (BBB), inflammatory response, mitochondrial dysfunction, and oxidative stress. Various biomarkers have been reported as potential diagnostic biomarkers for TBI, including neuron-specific enolase (NSE), S100B, neurofilament proteins (NFs), and tau proteins. Identifying the role of biomarkers in the diagnosis of TBI in children is challenging due to age-dependent baselines, sampling limitations, and funding gaps. Future research should focus more on investigating kinetics of TBI biomarkers before their application in clinical settings.